2017
DOI: 10.1007/s10792-017-0577-4
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of meibomian gland dysfunction in patients with Sjögren’s syndrome, non-Sjögren’s dry eye, and non-dry eye controls

Abstract: Patients in both SS and non-SS groups exhibited greater impairment in meibomian gland function than the non-dry eye controls. SS patients had more severe meibomian gland dysfunction with poorer mean meiboscore and meibomian gland expressibility than non-SS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 23 publications
2
37
2
2
Order By: Relevance
“…This suggests that the meibomian gland function cannot be maintained without an anti-inflammatory drug. In addition, patients with SID had a higher meiboscore than those without SID (P ¼ 0.0244), suggesting that meibomian gland dysfunction is more severe in patients with SID than in those without SID, being consistent with previous publications [31][32][33]. However, further studies are still needed to elucidate how meibomian gland cells are affected by inflammatory cells and to develop an effective method to protect the meibomian gland function.…”
Section: Outcome Of Patients With Sidsupporting
confidence: 86%
“…This suggests that the meibomian gland function cannot be maintained without an anti-inflammatory drug. In addition, patients with SID had a higher meiboscore than those without SID (P ¼ 0.0244), suggesting that meibomian gland dysfunction is more severe in patients with SID than in those without SID, being consistent with previous publications [31][32][33]. However, further studies are still needed to elucidate how meibomian gland cells are affected by inflammatory cells and to develop an effective method to protect the meibomian gland function.…”
Section: Outcome Of Patients With Sidsupporting
confidence: 86%
“…In 1998, Shimazaki et al [10] first reported that meibomian gland dropout of the lower eyelid was greater in SS patients than in non-SS dry eye patients, and 11 (57.9%) of 19 eyes exhibited gland dropout in more than half of the tarsus, but they neglected gland dropout of the upper eyelid. Menzies et al [6] and Kang et al [21] demonstrated that meibomian gland dropout was greater in SS patients' eyes than that in normal eyes overall (upper + lower), but this result was not demonstrated for separate areas. In conventional methods, meibomian gland expressibility is assessed by applying digital pressure on the upper tarsus, and in previous studies using this method, positive results were obtained [6,11].…”
Section: Discussionmentioning
confidence: 96%
“…Studies have reported that the volume (20), stability, lipid layer (21) and surface activity (22) of tears in SS patients decreased, while tear film evaporation (23), ocular surface damage (22) and symptoms of DED (8) increased. Researches also revealed that the meibomian glands have decreased expression and quality (24), and meibomian gland dropout and dysfunction are increased in subjects with Sjogren's Syndrome (10,21). However, up to now, no study has unveiled the relationship between the two important glands that were closely associated with dry eye, lacrimal and meibomian glands, in pSS patients.…”
Section: Discussionmentioning
confidence: 99%